Providing a ''Leg Up'': Parental Involvement and Opportunity Hoarding in College. Issue 2 (April 2018) - Hamilton, Laura; Roksa, Josipa; Nielsen, Kelly
Although higher education scholars are increasingly exploring disparities within institutions, they have yet to examine how parental involvement contributes to social-class variation in students' experiences. We ask, what role do parents play in producing divergent college experiences for students from different class backgrounds? Relying on interviews with 41 families, including mothers, fathers, and their daughters, we find that affluent parents serve as a ''college concierge, '' using class resources to provide youth with academic, social, and career support and access to exclusive university infrastructure. Less affluent parents, instead, describe themselves as ''outsiders'' who are unable to help their offspring and find the university unresponsive to their needs. Our findings suggest that affluent parents distinguish their children's college experiences from those of peers, extending ''effectively maintained inequality'' beyond the K-12 education. Universities may be receptive of these efforts due to funding shifts that make recruiting affluent, out-of-state families desirable.